Optimizing tiller production and survival for grain yield improvement in a bread wheat × spelt mapping population - Xie, Quan; Mayes, Sean; Sparkes, Debbie L. (Oxford Journals, 2015)
Background and Aims: Tiller production and survival determine final spike number, and play key roles in grain yield formation in wheat (Triticum aestivum). This study aimed to understand the genetic and physiological basis of the tillering process, and its trade-offs with other yield components, by introducing genetic variation in tillering patterns via a mapping population of wheat × spelt (Triticum spelta). Methods: The dynamics of tillering and red/far-red ratio (R:FR) at the base of a canopy arising from neighbouring plants in a bread wheat (Triticum aestivum ‘Forno’) × spelt (Triticum spelta ‘Oberkulmer’) mapping population were measured in the field in two growing seasons. Additional thinning and shading experiments were conducted in the field and glasshouse, respectively. Yield components were analysed for all experiments, followed by identification of quantitative trait loci (QTL) associated with each trait. Key Results Large genetic variation in tillering was observed, and more fertile shoots per plant were associated with more total shoots initiated, faster tillering rate, delayed tillering onset and cessation, and higher shoot survival. A total of 34 QTL for tillering traits were identified, and analysis of allelic effects confirmed the above associations. Low R:FR was associated with early tillering cessation, few total shoots, high infertile shoot number and shoot abortion, and these results concurred with the thinning and shading experiments. These effects probably resulted from an assimilate shortage for tiller buds or developing tillers, due to early stem elongation and enhanced stem growth induced by low R:FR. More fertile tillers normally contributed to plant yield and grain number without reducing yield and grain set of individual shoots. However, there was a decrease in grain weight, partly because of smaller carpels and fewer stem water-soluble carbohydrates at anthesis caused by pleiotropy or tight gene linkages. Conclusions: Tillering is under the control of both genetic factors and R:FR. Genetic variation in tillering and tolerance to low R:FR can be used to optimize tillering patterns for yield improvement in wheat.